Socio-economics of figure skating : Finnish figure skating families' socio-economic standing and perceptions of their child's participation in figure skating - Salonen, Rosa-Maria (2020)
As frequently addressed in media, sport culture is facing a problem where money is becoming one of the main barriers for participating in organized sports. Very often the most expensive sports happen to be the sports that children desperately want to join. The recent evidence suggests that membership fees in youth sports in Finland are roughly two to three times as expensive as they were ten years ago. One of the most expensive sports to participate in Finland is figure skating. Each year, as the figure skater advances higher level and the cost of figure skating continues to rise, more families are faced with the question of how to continue to keep their children active in the sport. The overall financial burden on families keeps many children from participating in figure skating. During the recent years, high costs and the accessibility to the sport has been under discussion. This study explores the linkage between figure skating and socio-economic background of the families whose children participate regularly in figure skating. The purpose is to demonstrate whether the barriers to participate in figure skating are purely dependent on family’s socio-economic background, and to understand figure skating families more accurately. Through various insights and perceptions from the parents’ point of view, this study gathered up-dated information of contemporary figure skating culture covering topics related to family background, family life and expenses. There is not any similar published studies within the families whose children practices figure skating. The data for this quantitative research was gathered through web-based online survey during the spring of 2019. Participants were the parents whose child is a member of the Finnish Figure Skating Association. The survey was sent to the parents through the Finnish Figure Skating email distributor and a total of 1763 parents completed an anonymous questionnaire. According to the results of this study, the overwhelming majority of respondents were most commonly married middle-aged mothers. Their children were mostly young 11-year-old girls who participated in competitive level single or synchronized skating. The majority of skating families had a high educational background, occupational status and an annual household income greater than 80 000 euros. Higher level of household income was associated with increased rates of competitive level skaters. Most of the parents reported to spend annually between 1 000 to 3 000 euros in figure skating club’s membership and license fees and less than 499 euros on extra fees. Although, figure skating expenses were perceived high affecting on family’s finances and leisure time decisions, parents reported the cost not being a barrier if their child advances to a higher level requiring them to pay more. Parents were highly involved in following and supporting their child’s skating performances but less likely to be involved in figure skating club’s fundraising activities.